Die Psalmen Davids, neu übersetzt und in Reime gebracht - Jorissen, Matthias 1739-1823 (Elberfeld Lucas, 1837)
Matthias Jorissen is best known for his 'Neue Bereimung der Psalmen', written around 1793 and published in 1798. This new, linguistically more modern rendition of the Psalms offers a careful translation of the biblical text, based on the classical melodies of the Genevan Psalter.
All Psalms are printed with the melody at the first verse, and the rest of the verses with only text.
Bound in with 'Des neuverbesserten Kirchen-Gesangbuchs' (1827) / 'Neue Sammlung auserlesener geistlicher Lieder' (1827), and 'Der Heidelberger Katechismus' (1827).
Includes lphabetical index of psalms
Ex libris J. P. Königs 1844 (gilt lettering on back and inside front cover)
Black leather cover with gilt lettering and some minor decorations
Von Matth. Jorissen Hochd. Pred. in Grafenhaag in Holland
Keywords: 19th Century (1801-1900); Calvinism; Psalm; Germany